A look at regional development since the Zapatista Movement (Mexico) (PerCursos, 2025)
Regional development as a field of study has been recognized as a fact (positive dimension) and as a strategy (normative dimension), whose propositional paths diverge from one another, incorporating the regulatory functions of the Market and/or admitting the action of the State. The aim of this article is to analyze the autonomy revealed by the Zapatista Movement (Mexico) based on some of its social self-determination practices. In analyzing the information, the use of indirect documentation stands out, with the bibliographic-documentary method being privileged in the review of literature and documents. The results show that one possibility regarding the permanent creation of regional disparities would be organized based on the recognition of autonomy by the social movements themselves. After 30 years since its constitution, the autonomy instilled in the state of Chiapas by the Zapatista Movement is being permanently rebuilt through an integrated and participatory hierarchical structure, making room for new autonomies after years of maturation, successes, mistakes, construction and consolidation.
Keywords: social movements; regional development; Mexico; Zapatista Movement